A new quinolone alkaloid from the fruits of Tetradium ruticarpum. Issue 2 (17th January 2021) - Ma, Chen; Liu, Xiao; Shan, Yu; Xu, Shu; Feng, Xu; Wang, Qi-Zhi
Abstract: A rare new quinolone alkaloid containing three degrees of unsaturation in the side chain, named as 1-methyl-2-[(6 Z, 9 Z, 12 Z )-6, 9, 12-pentadecatriene]-4( 1H )-quinolone (1 ), together with three known quinolone alkaloids 1-methyl-2-[(6 Z, 9 Z )-6, 9-pentadecadienyl]-4( 1H )-quinolone (2 ), 1-methyl-2-[(4 Z, 7 Z )-4, 7-tridecadienyl]-4( 1H )-quinolone (3 ), 1-methyl-2-[( Z )-8-tridecenyl]-4( 1H )-quinolone (4 ), were isolated from the fruits of Tetradium ruticarpum (A.Juss.) T.G.Hartley. Their structures were elucidated by physicochemical properties and spectroscopic data. All compounds were evaluated for their cytotoxic activities against three human tumor cell lines, including Lovo, MDA-MB-231, HeLa cells, by MTT method in 96-well microplates, and compounds 1 exhibited potent activity against MDA-MB-231 cells with IC50 values of 7.95 μM. GRAPHICAL ABSTRACT: